PENGEMBANGAN MEDIA BERBASIS POWTOON PADA PELAJARAN PPKN KELAS III SD - Cindy Junita Carolin; Muhammad Idris; Hermansyah (LPPM Universitas Cipta Mandiri, 2024)
This research aims to produce the development of powtoon-based media in PPKN learning that is valid and practical. To determine the effectiveness of using powtoon-based media for class III students. This research uses the Research and Development (R&D) method with the ADDIE development model. Questionnaire, test and documentation data collection techniques. Data analysis techniques with validity, practicality and effectiveness criteria. The results of this research show that the development of powtoon-based media in Civics learning, material on my obligations and rights, sub-theme 2, my obligations and rights at school for class III students at SD Negeri 94 Palembang is stated: valid, the results of the validity assessment according to media experts are an average score of 4.3 percentage 86.2%, linguists got an average score of 4.1, a percentage of 82% and material experts got an average score of 4.4, a percentage of 88.3%. Practically based on the results of the practicality assessment according to the student response questionnaire, students got an average score of 4.4 with a percentage of 90.2%. Based on the assessment of the effectiveness of student evaluation results, students obtained a total average score of 7.4 with a percentage of 74%. So it can be concluded that Powtoon-based media in Civics learning is declared valid, practical and effective.